Trophic assessment of four tropical reservoirs using phytoplankton genera - Carlos A. Rivera; Angela Zapata; William Villamil; Nubia León-López (Acta Limnologica Brasiliensia, 2022)
Abstract: Aim Monitoring the trophic state of reservoirs requires indices that provide a quick report of the ecosystem to decision makers. This study aimed to develop a system of trophic status indicators for tropical mountain reservoirs using phytoplankton genera. Methods Between 2004 and 2010, four reservoirs for water supply in Bogotá (Colombia), which have different trophic statuses and hydraulic management, were monitored. Samples were collected for the analysis of physical and chemical variables and phytoplankton community. Through multivariate analysis, the significance of the relationships between environmental variables and phytoplankton species and genera was established. Subsequently, trophic indices were proposed as relevant variables. The global trophic index was calculated as the sum of the partial indices. Results Analysis of the main components showed that reservoirs varied chemically depending on trophic status. Phytoplankton were composed of 63 genera, 59% of which were present in the four reservoirs. Although the physical characteristics of water, such as temperature and total solids content, explained a large part of the variation in the genera, a significant relationship between the genera and variables related to trophic state was observed in each reservoir. The multivariate analyses grouping the data by genera showed a behavior similar to the analysis using information at the species level. Plankton indices of trophic state were developed for phosphorus (TP), total Kjeldahl nitrogen (TKN), total organic carbon (TOC), and Secchi disk (SD) using data grouped by genera. The indices were significantly correlated with the values of each variable in each reservoir. Linear regression models showed a significant prediction of chlorophyll-a using TP, TKN, and SD indices in the three reservoirs with the highest trophic level. In addition, the global index showed a significant relationship with variables related to the trophic state. Conclusions Phytoplankton data at the genus level can be used to assess trophic status. The models for SD, TP, and TKN could be used as indicators of the trophic status of the studied reservoirs.